Industrial vehicle lithium iron phosphate battery water-based positive electrode slurry and preparation method thereof
By adopting aqueous positive electrode slurry and a double planetary mixer multiple dispersion steps, the environmental and health risks of NMP solvents are solved, and the good dispersion and high stability of the positive electrode slurry of lithium iron phosphate battery is achieved, reducing the internal resistance of the battery cell and improving the Battery performance.
Patent Information
- Application Number
- CN202411395436.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-14
AI Technical Summary
The existing lithium iron phosphate battery positive electrode slurry uses flammable and explosive and harmful to the environment and health, resulting in environmental pollution and health risks, and it is difficult to achieve good dispersion and high stability.
Using aqueous positive electrode slurry, containing lithium iron phosphate, conductive agent, water-based binder and conductive paste, multiple dispersion and defoaming steps are used for the dual planetary mixer, and the solid content and viscosity are increased by deionized water to achieve uniform dispersion and stability.
It reduces environmental pollution and health risks, improves the dispersion and stability of lithium iron phosphate positive electrode slurry, reduces the internal resistance of the battery cell and improves the rate performance of the battery cell, and meets the coating requirements.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery slurry preparation, and in particular to an aqueous positive electrode slurry for lithium iron phosphate batteries of industrial vehicles and a preparation method thereof. Background Art
[0002] With the rapid development of the automobile industry, environmentally friendly electric vehicles have become a new trend in automobile energy conservation and emission reduction. With the improvement of safety and performance and the reduction of cost, power lithium-ion batteries are increasingly showing strong vitality, and will also bring a vibrant future to related companies.
[0003] Among the existing related technologies, lithium-ion batteries with LFP (lithium iron phosphate) as the positive electrode material have obvious comprehensive performance advantages due to their low DSC exothermic peak, high overcharge voltage resistance, good safety performance, and high power cycle life at high temperatures. At the same time, due to the rich resources of raw and auxiliary materials used in the manufacture of lithium iron phosphate batteries and low production costs, they have obvious cost advantages. Therefore, lithium iron phosphate batteries have become the main direction of the development of power batteries.
[0004] In order to ensure the performance of lithium iron phosphate batteries, lithium iron phosphate positive electrode slurry must have good dispersion and high stability. Therefore, in order to better disperse lithium iron phosphate particles and reduce the occurrence of agglomeration, the current mainstream production method of lithium iron phosphate positive electrode slurry uses oil-based slurry for stirring, that is, using N-methylpyrrolidone (NMP) as a solvent.
[0005] Regarding the above-mentioned related technologies, NMP is highly volatile, making it flammable, explosive and toxic, and is likely to have a negative impact on the environment and human health. Summary of the invention
[0006] In order to prepare a lithium iron phosphate positive electrode slurry with good dispersibility and high stability under the premise of reducing the negative impact on the environment and personnel health, the present application provides an aqueous positive electrode slurry for lithium iron phosphate batteries of industrial vehicles.
[0007] The aqueous positive electrode slurry of an industrial vehicle lithium iron phosphate battery provided in this application adopts the following technical solution: An aqueous positive electrode slurry for lithium iron phosphate batteries of industrial vehicles, composed of the following weight fractions: 93.0-96.0% lithium iron phosphate, 1.0-3.0% conductive agent, 1.0-4.0% aqueous binder, and 0.5-2.0% conductive slurry; The solvent of the positive electrode slurry is deionized water, and the solid content of the positive electrode slurry is 58±5%.
[0008] Optionally, the conductive agent is at least one of acetylene black, carbon black, Ketjen black and carbon nanotubes.
[0009] Optionally, the aqueous binder is of polyacrylic acid type.
[0010] Optionally, the conductive paste is a graphene composite conductive paste or a carbon nanotube conductive paste.
[0011] Optionally, the conductivity of the deionized water is less than or equal to 2 μs / cm.
[0012] Optionally, the solid content of the conductive paste is 58±5%, and the viscosity of the conductive paste is 5000-8000 Pa·s.
[0013] The present application also provides a method for preparing an aqueous positive electrode slurry for an industrial vehicle lithium iron phosphate battery, which adopts the following technical solution: A method for preparing an aqueous positive electrode slurry for an industrial vehicle lithium iron phosphate battery comprises the following steps: S1, mixing, adding lithium iron phosphate and conductive agent into a double planetary mixer for stirring; the dispersion speed of the double planetary mixer is 400-500rpm, the revolution speed of the double planetary mixer is 15-20rpm, and the stirring time of the double planetary mixer is 20-30min; S2, primary dispersion, adding an aqueous binder, a conductive slurry and a portion of deionized water to the mixed material in step S1, and making the solid content of the slurry 70-75%; The double planetary mixer is first stirred at a dispersion speed of 500 rpm, a revolution speed of 10-12 rpm and a stirring time of 10-20 min, and then stirred at a dispersion speed of 3500-4000 rpm, a revolution speed of 35-40 rpm and a stirring time of 90-120 min; S3, secondary dispersion, adding deionized water to the mixture in step S2, and making the solid content of the slurry 65-68%; The dispersion speed of the double planetary mixer is 3500-4000rpm, the revolution speed of the double planetary mixer is 35-40rpm, and the stirring time of the double planetary mixer is 60min; S4, dispersing three times, adding another portion of deionized water to the mixture in step S3, and making the solid content of the slurry 58±3%; The dispersion speed of the double planetary mixer is 3500-4000rpm, the revolution speed of the double planetary mixer is 35-40rpm, and the stirring time of the double planetary mixer is 20-40min; S5, degassing, stopping the dispersion and stirring of the double planetary mixer, and reversing the double planetary mixer at an orbital speed of 10-15 rpm; The vacuum degree for the degassing is -0.08-0.09Mpa, and the degassing time is 50-60min.
[0014] In summary, the present application includes at least one of the following beneficial technical effects: Water is used to increase the fluidity of the positive electrode slurry and reduce the viscosity of the conductive slurry, making it easier to disperse the boredom evenly; In the steps S2 and S3, the solid content of the slurry is relatively high, so that the viscosity of the slurry is relatively high, making it easier for the material to be evenly wrapped, reducing the occurrence of uneven or unstable slurry dispersion due to poor wettability of the material with water, thereby making the slurry evenly dispersed and more stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a bar chart comparing the internal resistance of Examples 1-3 and Comparative Examples 1-2 of the present application.
[0016] Figure 2 It is a line graph of the 2C discharge capacity retention rate of Examples 1-3 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION
[0017] The following is combined with Figure 1-2 This application is described in further detail. Example
[0018] Example 1 of the present application discloses an aqueous positive electrode slurry for a lithium iron phosphate battery for industrial vehicles, which is composed of the following weight fractions: 95.0% lithium iron phosphate, 1.5% conductive agent, 2.5% aqueous binder, and 1.0% conductive slurry.
[0019] In this embodiment 1, the aqueous positive electrode slurry of the lithium iron phosphate battery for industrial vehicles is prepared according to the following steps: S1. Mixing: adding lithium iron phosphate and conductive agent into a double planetary mixer for mixing; Specifically, the conductive agent is at least one of acetylene black, carbon black, Ketjen black and carbon nanoparticles, and in Example 1 of the present application, the conductive agent is SP (carbon black) powder. The dispersion speed of the double planetary mixer is 400 rpm, the revolution speed is 15 rpm, and the stirring time is 20 min.
[0020] S2, primary dispersion, adding an aqueous binder, a conductive slurry and a portion of deionized water to the mixed material in step S1, and making the solid content of the slurry 72%; Specifically, the aqueous binder is a polyacrylic acid, and in Example 1 of the present application, the aqueous binder is the ADY-7012 binder of Hubei Kediya Technology Co., Ltd. The solid content of the conductive slurry is 58±5% and the viscosity is 5000-8000Pa·s, and the conductive slurry is a graphene composite conductive slurry or a carbon nanotube conductive slurry, and in Example 1 of the present application, the conductive slurry is a graphene composite conductive slurry. The conductivity of deionized water is less than or equal to 2μs / cm. The double planetary mixer is first stirred at a dispersion speed of 500rpm, an orbital speed of 10rpm and a stirring time of 10min, and then the double planetary mixer is stirred at a dispersion speed of 3500rpm, an orbital speed of 35rpm and a stirring time of 90min.
[0021] S3, secondary dispersion, adding deionized water to the mixture in step S2, and making the solid content of the slurry 65%; Specifically, the dispersion speed of the double planetary mixer is 3500 rpm, the revolution speed is 35 rpm and the stirring time is 60 min.
[0022] S4, tertiary dispersion, adding another portion of deionized water to the mixture in step S3, and making the solid content of the slurry 60% and the discharge viscosity 6000mpa·s; Specifically, the dispersion speed of the double planetary mixer is 3500 rpm, the revolution speed is 35 rpm and the stirring time is 30 min.
[0023] S5, degassing, stopping the dispersion and stirring of the double planetary mixer, and reversing the double planetary mixer at an orbital speed of 15 rpm; Specifically, the vacuum degree for degassing is -0.085 MPa, and the degassing time is 60 minutes. Example
[0024] Example 2 of the present application discloses an aqueous positive electrode slurry for a lithium iron phosphate battery for industrial vehicles, which is composed of the following weight fractions: 94.0% lithium iron phosphate, 1.5% conductive agent, 3.0% aqueous binder, and 1.5% conductive slurry.
[0025] In this embodiment 2, the aqueous positive electrode slurry of the lithium iron phosphate battery for industrial vehicles is prepared according to the following steps: S1. Mixing: adding lithium iron phosphate and conductive agent into a double planetary mixer for mixing; Specifically, the conductive agent is SP powder. The dispersion speed of the double planetary mixer is 400 rpm, the revolution speed is 15 rpm, and the stirring time is 20 min.
[0026] S2, primary dispersion, adding an aqueous binder, a conductive slurry and a portion of deionized water to the mixed material in step S1, and making the solid content of the slurry 73%; Specifically, the water-based binder is BA-306F binder from Fujian Blue Sea Black Stone New Material Technology Co., Ltd., the solid content of the conductive slurry is 58±5% and the viscosity is 5000-8000 Pa·s, the conductive slurry is a graphene composite conductive slurry, and the conductivity of deionized water is less than or equal to 2μs / cm. The double planetary mixer is first stirred at a dispersion speed of 500rpm, a revolution speed of 10rpm, and a stirring time of 10min, and then the double planetary mixer is stirred at a dispersion speed of 4000rpm, a revolution speed of 40rpm, and a stirring time of 60min.
[0027] S3, secondary dispersion, adding deionized water to the mixture in step S2, and making the solid content of the slurry 68%; Specifically, the dispersion speed of the double planetary mixer is 4000 rpm, the revolution speed is 40 rpm and the stirring time is 60 min.
[0028] S4, tertiary dispersion, adding another portion of deionized water to the mixture in step S3, and making the solid content of the slurry 58% and the discharge viscosity 7500mpa·s; Specifically, the dispersion speed of the double planetary mixer is 4000 rpm, the revolution speed is 40 rpm and the stirring time is 30 min.
[0029] S5, degassing, stopping the dispersion and stirring of the double planetary mixer, and reversing the double planetary mixer at an orbital speed of 15 rpm; Specifically, the vacuum degree for degassing is -0.090 MPa, and the degassing time is 60 minutes. Example
[0030] Example 3 of the present application discloses an aqueous positive electrode slurry for a lithium iron phosphate battery for industrial vehicles, which is composed of the following weight fractions: 96.0% lithium iron phosphate, 1.0% conductive agent, 2.0% aqueous binder, and 1.0% conductive slurry.
[0031] The aqueous positive electrode slurry of the lithium iron phosphate battery for industrial vehicles in this embodiment 3 is prepared according to the following steps: S1. Mixing: adding lithium iron phosphate and conductive agent into a double planetary mixer for mixing; Specifically, the conductive agent is SP powder. The dispersion speed of the double planetary mixer is 400 rpm, the revolution speed is 15 rpm, and the stirring time is 20 min.
[0032] S2, primary dispersion, adding an aqueous binder, a conductive slurry and a portion of deionized water to the mixed material in step S1, and making the solid content of the slurry 71%; Specifically, the water-based binder is ADY-7012 binder of Hubei Kediya Technology Co., Ltd., the solid content of the conductive slurry is 58±5% and the viscosity is 5000-8000Pa·s, the conductive slurry is a graphene composite conductive slurry, and the conductivity of deionized water is less than or equal to 2μs / cm. The double planetary mixer is first stirred at a dispersion speed of 400rpm, a revolution speed of 10rpm and a stirring time of 20min, and then the double planetary mixer is stirred at a dispersion speed of 3500rpm, a revolution speed of 35rpm and a stirring time of 60min.
[0033] S3, secondary dispersion, adding deionized water to the mixture in step S2, and making the solid content of the slurry 63%; Specifically, the dispersion speed of the double planetary mixer is 3500 rpm, the revolution speed is 35 rpm and the stirring time is 60 min.
[0034] S4, tertiary dispersion, adding another portion of deionized water to the mixture in step S3, and making the solid content of the slurry 56% and the discharge viscosity 6200mpa·s; Specifically, the dispersion speed of the double planetary mixer is 3500 rpm, the revolution speed is 35 rpm and the stirring time is 30 min.
[0035] S5, degassing, stopping the dispersion and stirring of the double planetary mixer, and reversing the double planetary mixer at an orbital speed of 15 rpm; Specifically, the vacuum degree for degassing is -0.085 MPa, and the degassing time is 60 minutes.
[0036] Comparative Example 1: Comparative Example 1 of the present application discloses an aqueous positive electrode slurry for lithium iron phosphate batteries of industrial vehicles, which is composed of the following weight fractions: 94.0% lithium iron phosphate, 1.0% conductive agent, 2.5% aqueous binder, and 2.5% conductive slurry.
[0037] In this comparative example 1, the aqueous positive electrode slurry of the lithium iron phosphate battery for industrial vehicles was prepared according to the following steps: S1. Mixing: adding lithium iron phosphate and conductive agent into a double planetary mixer for mixing; Specifically, the conductive agent is a mixture of SP powder and KS-6 (graphite) powder. The double planetary mixer has a dispersion speed of 400 rpm, a revolution speed of 15 rpm, and a stirring time of 20 min.
[0038] S2, primary dispersion, adding an aqueous binder, a conductive slurry and a portion of deionized water to the mixed material in step S1, and making the solid content of the slurry 72%; Specifically, the water-based binder is ADY-7012 binder of Hubei Kediya Technology Co., Ltd., the solid content of the conductive slurry is 58±5% and the viscosity is 5000-8000Pa·s, the conductive slurry is a graphene composite conductive slurry, and the conductivity of deionized water is less than or equal to 2μs / cm. The double planetary mixer is first stirred at a dispersion speed of 500rpm, a revolution speed of 10rpm and a stirring time of 10min, and then the double planetary mixer is stirred at a dispersion speed of 3500rpm, a revolution speed of 35rpm and a stirring time of 90min.
[0039] S3, secondary dispersion, adding deionized water to the mixture in step S2, and making the solid content of the slurry 65%; Specifically, the dispersion speed of the double planetary mixer is 3500 rpm, the revolution speed is 35 rpm and the stirring time is 60 min.
[0040] S4, tertiary dispersion, adding another portion of deionized water to the mixture in step S3, and making the solid content of the slurry 58% and the discharge viscosity 5760mpa·s; Specifically, the dispersion speed of the double planetary mixer is 3500 rpm, the revolution speed is 35 rpm and the stirring time is 30 min.
[0041] S5, degassing, stopping the dispersion and stirring of the double planetary mixer, and reversing the double planetary mixer at an orbital speed of 15 rpm; Specifically, the vacuum degree for degassing is -0.085 MPa, and the degassing time is 60 minutes.
[0042] Comparative Example 2: Comparative Example 2 of the present application discloses an aqueous positive electrode slurry for lithium iron phosphate batteries of industrial vehicles, which is composed of the following weight fractions: 94.0% lithium iron phosphate, 1.5% conductive agent, 3.0% aqueous binder, and 1.5% conductive slurry.
[0043] The aqueous positive electrode slurry of the lithium iron phosphate battery for industrial vehicles in this comparative example 2 was prepared according to the following steps: S1. Mixing: adding lithium iron phosphate and conductive agent into a double planetary mixer for mixing; Specifically, the conductive agent is SP and KS-6, i.e., graphite. The dispersion speed of the double planetary mixer is 400 rpm, the revolution speed is 15 rpm, and the stirring time is 20 min.
[0044] S2, primary dispersion, adding water-based binder, conductive slurry and NMP to the mixed material in step S1, and making the solid content of the slurry 73%; Specifically, the water-based binder is BA-306F binder from Fujian Blue Sea Black Stone New Material Technology Co., Ltd., the solid content of the conductive slurry is 58±5% and the viscosity is 5000-8000 Pa·s, the conductive slurry is carbon nanotube conductive slurry, and the conductivity of deionized water is less than or equal to 2μs / cm. The double planetary mixer is first stirred at a dispersion speed of 500rpm, a revolution speed of 10rpm and a stirring time of 10min, and then the double planetary mixer is stirred at a dispersion speed of 4000rpm, a revolution speed of 40rpm and a stirring time of 60min.
[0045] S3, secondary dispersion, adding NMP to the mixture in step S2, and making the solid content of the slurry 65%; Specifically, the dispersion speed of the double planetary mixer is 3500 rpm, the revolution speed is 35 rpm and the stirring time is 60 min.
[0046] S4, tertiary dispersion, adding the remaining NMP to the mixed material in step S3, and making the solid content of the slurry 63% and the discharge viscosity 7860mpa·s; Specifically, the dispersion speed of the double planetary mixer is 4000 rpm, the revolution speed is 40 rpm and the stirring time is 30 min.
[0047] S5, degassing, stopping the dispersion and stirring of the double planetary mixer, and reversing the double planetary mixer at an orbital speed of 15 rpm; Specifically, the vacuum degree for degassing is -0.090 MPa, and the degassing time is 60 minutes.
[0048] The slurries prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2 were made into battery cells through subsequent processes for internal resistance and electrical performance tests. The results are shown in Table 1: Refer to Table 1. Figure 1 as well as Figure 2 , the viscosity range of the lithium iron phosphate positive electrode slurry meets the coating requirements, the internal resistance of Examples 1-3 is significantly less than 0.32mΩ of Comparative Example 1, and the 2C discharge capacity retention rate is 1.7% higher. Therefore, using water as a solvent reduces production costs and environmental pollution, and a lithium iron phosphate positive electrode slurry with good dispersibility and high stability is prepared under the premise of reducing the negative impact on the environment and personnel health. In addition, the addition of the conductive slurry significantly reduces the internal resistance of the battery cell and improves the rate performance of the battery cell.
[0049] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. An aqueous positive electrode slurry for lithium iron phosphate batteries for industrial vehicles, characterized in that: Composition by weight: lithium iron phosphate 93.0-96.0%, conductive agent 1.0-3.0%, aqueous binder 1.0-4.0%, conductive paste 0.5-2.0%; The solvent of the positive electrode slurry is deionized water, and the solid content of the positive electrode slurry is 58±5%.
2. The aqueous positive electrode slurry for lithium iron phosphate battery of industrial vehicles according to claim 1, characterized in that: The conductive agent is at least one of acetylene black, carbon black, Ketjen black and carbon nanotubes.
3. The aqueous positive electrode slurry for lithium iron phosphate battery of industrial vehicles according to claim 1, characterized in that: The type of the aqueous binder is polyacrylic acid.
4. The aqueous positive electrode slurry for lithium iron phosphate battery of industrial vehicles according to claim 1, characterized in that: The conductive paste is a graphene composite conductive paste or a carbon nanotube conductive paste.
5. The aqueous positive electrode slurry for lithium iron phosphate battery of industrial vehicles according to claim 1, characterized in that: The conductivity of the deionized water is less than or equal to 2 μs / cm.
6. The aqueous positive electrode slurry for lithium iron phosphate battery of industrial vehicles according to claim 1, characterized in that: The solid content of the conductive paste is 58±5%, and the viscosity of the conductive paste is 5000-8000 Pa·s.
7. A method for preparing aqueous positive electrode slurry for lithium iron phosphate batteries for industrial vehicles, characterized in that: Used to prepare the aqueous positive electrode slurry of the lithium iron phosphate battery for industrial vehicles according to any one of claims 1 to 6, and comprising the following steps: S1, mixing, adding lithium iron phosphate and conductive agent into a double planetary mixer for stirring; the dispersion speed of the double planetary mixer is 400-500rpm, the revolution speed of the double planetary mixer is 15-20rpm, and the stirring time of the double planetary mixer is 20-30min; S2, primary dispersion, adding an aqueous binder, a conductive slurry and a portion of deionized water to the mixed material in step S1, and making the solid content of the slurry 70-75%; The double planetary mixer is first stirred at a dispersion speed of 500 rpm, a revolution speed of 10-12 rpm and a stirring time of 10-20 min, and then stirred at a dispersion speed of 3500-4000 rpm, a revolution speed of 35-40 rpm and a stirring time of 90-120 min; S3, secondary dispersion, adding deionized water to the mixture in step S2, and making the solid content of the slurry 65-68%; The dispersion speed of the double planetary mixer is 3500-4000rpm, the revolution speed of the double planetary mixer is 35-40rpm, and the stirring time of the double planetary mixer is 60min; S4, dispersing three times, adding another portion of deionized water to the mixture in step S3, and making the solid content of the slurry 58±3%; S5, degassing, stopping the dispersion and stirring of the double planetary mixer, and reversing the double planetary mixer at an orbital speed of 10-15 rpm; The vacuum degree for the degassing is -0.08-0.09Mpa, and the degassing time is 50-60min.
Citation Information
Patent Citations
CNT-containing lithium ion battery waterborne positive electrode paste and preparation method therefor
CN105552367A
Water-soluble lithium battery cathode slurry mixing process
CN112838210A
Positive electrode slurry and preparation method and application thereof
CN114335541A
Aqueous lithium iron phosphate battery
CN114497699A
Aqueous iron-lithium positive plate and preparation method thereof
CN115472765A